Assessment of probability of lightning direct strike into elements of stationary ground launch complex (англійською мовою) - Kniaziev, Volodymyr Volodymyrovych; Melnik, Sergiy Ivanovych (НТУ "ХПИ", 2018)
Materials presented in the paper are the first stage of realization of methodology of ensuring the required level of protection of rocket space complexes from destabilizing action of lightning. The methodology is an obligatory element of ensuring a life cycle of the complexes and is logically integrated into the system of standards of IEC 61508 series. The presented first stage includes a calculated estimation of probability of lightning direct strike into elements of the complex. The estimation was carried out with using a method based on calculation of distribution of intensity of stationary electric field over the surface of objects of the complex. It is shown that it is sufficient to use only a variant of vertical, in relation to the ground surface, vector of intensity of electric field created by a thundercloud.

Материалы, представленные в докладе являются первым этапом реализации методологии обеспечения требуемого уровня защиты ракетных космических комплексов от дестабилизирующего действия молнии. Методология является обязательным элементом обеспечения жизненного цикла комплексов и логично встраивается в систему стандартов серии IEC 61508. Представленный первый этап включает расчетную оценку вероятности прямого удара молнии в элементы комплекса. Оценка проведена с использованием метода, основанного на расчете распределения напряженности стационарного электрического поля по поверхности объектов комплекса. Показано, что достаточно использовать только вариант вертикального по отношению к поверхности земли вектора напряженности электрического поля, создаваемого грозовым облаком
Оценка вероятности прямого удара молнии в элементы стационарного наземного пускового комплекса
Keywords: lightning; rocket space complexes; probability; electric field; молния; космодром; вероятность; электрическое поле